Regulatory and Supervisory Independence and Financial Stability - Taylor, Michael (IMF Working Papers; Working Paper ;, 2002)
Despite its importance, the issue of financial sector regulatory and supervisory independence (RSI) has received only marginal attention in literature and practice. However, experience has demonstrated that improper supervisory arrangements have contributed significantly to the deepening of several recent systemic banking crises. In this paper we argue that RSI is important for financial stability for the same reasons that central bank independence is important for monetary stability. The paper lays out four key dimensions of RSI-regulatory, supervisory, institutional and budgetary-and discusses ways to achieve them. We also discuss institutional arrangements needed to make independence work in practice. The key issue in this respect is that agency independence and accountability need to go hand in hand. The paper discusses a number of accountability arrangements.